Identification of Age-Related Characteristic Genes Involved in Severe COVID-19 Infection Among Elderly Patients Using Machine Learning and Immune Cell Infiltration Analysis - Huan Li; Jin Zhao; Yan Xing; Jia Chen; Ziying Wen; Rui Ma; Fengxia Han; Boyong Huang; Hao Wang; Cui Li; Yang Chen; Xiaoxuan Ning (Biochemical Genetics, 2025)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

SLCO1B1 Polymorphisms are Associated with the Susceptibility to Pulmonary Tuberculosis in Chinese Females - Wei Li; Wei Liu; Xiong Wang; Rui Dou; Zunmin Zhu (Biochemical Genetics, 2024)

GABRP Promotes the Metastasis of Pancreatic Cancer by Activation of the MEK/ERK Signaling Pathway - Yong Meng; Rui Li; Shuaiming Geng; Wenhao Chen; Weirong Jiang; Zhiwen Li; Ji Hao; Zhen Xu (Biochemical Genetics, 2024)

Complete Genome Sequence of Streptomyces sp. HP-A2021, a Promising Bacterium for Natural Product Discovery - Lan-Fang Li; Qing-Xuan Wu; Hao Wu; Yao Li; Qian Peng; Ren-Hao Han; Da-Hu Zhang; Wei-Dong Yu; Rui Xu; Juan Wang; Zhaobin Fan; Shao-Yang Hou (Biochemical Genetics, 2023)

LncRNA BBOX1-AS1 Contributes to the Progression of Esophageal Carcinoma by Targeting the miR-361-3p/COL5A1 Axis - Yu-Hai Lu; Dong-Sheng He; Ying Li; Hong Wang; Rui-Dong Ma (Biochemical Genetics, 2023)

Genome-Wide Identification and Expression Analysis of the CAD Gene Family in Walnut (Juglans regia L.) - Pengyu Wu; Rui Zhang; Shangqi Yu; Jiazhi Fu; Zhongzhong Guo; Dong Li; Zhiyong Pan; Haifang Hu (Biochemical Genetics, 2023)

Circ_HIPK3 Inhibits H2O2-Induced Lens Epithelial Cell Injury in Age-Related Cataract Depending on the Regulation of miR-495-3p/HDAC4 Pathway - Sihui Chen; Minghong Wang; Rui Jian; Hui Li; Guoli Liu; Cuiyun Zhou; Yan Xiong; Wenqian Wang (Biochemical Genetics, 2023)

Constructing a Ferroptosis-related Long Non-coding RNA Signature to Predict the Prognostic of Head and Neck Squamous Cell Carcinoma Patients by Bioinformatic Analysis - Rui Lu; Zhiyong Li; Shucheng Yin (Biochemical Genetics, 2022)
Ferroptosis is a novel discovered iron-dependent mode of regulated cell death (RCD) which characterized non-apoptosis. Researches have shown the effect of ferroptosis in the biological activities of tumors. But there is no relevant study showing the relationship between ferroptosis-related genes and head and neck squamous cell carcinoma (HNSCC). In this study, we paid attention to several ferroptosis-related lncRNAs in head and neck squamous cell carcinoma and its clinical features. HNSCC data were obtained from The Cancer Genome Atlas (TCGA) database. Ferroptosis-related lncRNAs were selected by the coexpression network. Then, we identified prognostic ferroptosis-related lncRNAs in HNSCC patients and constructed a ferroptosis-related lncRNAs signature by Lasso cox regression. Besides, GSEA analysis was performed to explore the functional enrichment of ferroptosis-related lncRNAs. Nine ferroptosis-related lncRNAs (AC004687.1, AL450992.2, AC010894.2, AL451085.2, AC104083.1, LIPE-AS1, AC108010.1, CTBP1-DT, and PTCSC2) were identified to have the independent prognostic value in HNSCC patients and the ferroptosis-related lncRNAs signature was constructed based on these nine genes. According to the risk score of the signature, the high-risk group had shorter overall survival (OS) compared with the low-risk group. Risk score showed to be an independent factor for the patients with HNSCC. Additionally, the nomogram was generated and the nine lncRNAs were mainly enriched in phagocytosis, metabolism, and chemokine signaling pathways. The ferroptosis-related lncRNA signature has effects on the prognostic prediction of patients with HNSCC which may serve as potential therapeutic targets for patients with HNSCC.

miR-181b-5p Promotes the Progression of Cholangiocarcinoma by Targeting PARK2 via PTEN/PI3K/AKT Signaling Pathway - Zhe-Long Jiang; Fu-Xing Zhang; Hong-Liang Zhan; He-Jun Yang; Si-Yu Zhang; Zhao-Hui Liu; Yi Jiang; Li-Zhi Lv; Rui-Sheng Ke (Biochemical Genetics, 2022)

MicroRNA-363-3p Inhibits the Expression of Renal Fibrosis Markers in TGF-β1-Treated HK-2 Cells by Targeting TGF-β2 - Xiangnan Dong; Yang Li; Rui Cao; Honglan Xu (Biochemical Genetics, 2021)

MELK Accelerates the Progression of Colorectal Cancer via Activating the FAK/Src Pathway - Guangming Liu; Wei Zhan; Wei Guo; Feng Hu; Junjie Qin; Rui Li; Xin Liao (Biochemical Genetics, 2020)

De Novo Assembled Transcriptome Analysis and Identification of Genic SSR Markers in Red-Flowered Strawberry - Yan Ding; Li Xue; Rui-xue Guo; Gang-jun Luo; Yu-tong Song; Jia-jun Lei (Biochemical Genetics, 2019)

Relationships Among Genetic Makeup, Active Ingredient Content, and Place of Origin of the Medicinal Plant Gastrodia Tuber - Jun Tao; Zhi-yong Luo; Chikira Ismail Msangi; Xiao-shun Shu; Li Wen; Shui-ping Liu; Chang-quan Zhou; Rui-xin Liu; Wei-xin Hu (Biochemical Genetics, 2009)

Phylogenetic Analysis of Leymus (Poaceae: Triticeae) Inferred from Nuclear rDNA ITS Sequences - Li-na Sha; Rui-wu Yang; Xing Fan; Xiao-li Wang; Yong-hong Zhou (Biochemical Genetics, 2008)

A Study of Conservation Genetics in Cupressus chengiana, an Endangered Endemic of China, Using ISSR Markers - Bingqing Hao; Wang Li; Mu Linchun; Yao Li; Zhang Rui; Tang Mingxia; Bao Weikai (Biochemical Genetics, 2006)

Genetic diversity in the Chinese pangolin (Manis pentadactyla) inferred from protein electrophoresis - Bing Su; Rui-Qing Liu; Ying-xiang Wang; Li-ming Shi (Biochemical Genetics, 1994)

Genetic diversity in the Chinese pangolin (Manis pentadactyla) inferred from protein electrophoresis - Bing Su; Rui-Qing Liu; Ying-xiang Wang; Li-ming Shi (Biochemical Genetics, 1994)